The Effects of Online Incentivized Reviews on Organic Review Ratings - (:unkn) unknown (My University, 2020)
As online reviews become a major factor in the consumer decision-making process, firms have started seeking ways to create and leverage reviews to help achieve their marketing objectives. One productive strategy to generate reviews is to incentivize or reward customers to write reviews. While such a strategy certainly augments the number of reviews, it naturally raises questions of how unbiased such reviews are, and how such a "bias," if it exists, affects potential customers. Complicating the issue further, such incentives can be provided by either the vendor or the platform, which may affect the nature of "bias." To understand the marketing value of such reviews, this research examines the effects of online incentivized reviews on subsequent organic reviews. First, we investigate whether incentivized reviews are biased compared to organic reviews. Specifically, we find that vendor – initiated incentivized reviews are more favorable whereas platform – initiated incentivized reviews are more critical. Second, we study how incentivized reviews affect future organic review ratings. The findings suggest that vendor (platform) – initiated incentivized reviews reduce (increase) the subsequent organic review ratings. Moderating effects of helpfulness of incentivized reviews and product type are significant. These findings offer important insights about the effectiveness of incentivized reviews.